Fractals, wavelets, and their applications : contributions from the international conference and workshop on fractals and wavelets - Barnsley, Michael; Devaney, Robert; Falconer, Kenneth J.; Kannan, V.; Kumar P.B., Vinod; Bandt, Christoph (Springer Proceedings in Mathematics & Statistics, 2014)
Fractals and wavelets are emerging areas of mathematics with many common factors which can be used to develop new technologies. This volume contains the selected contributions from the lectures and plenary and invited talks given at the International Workshop and Conference on Fractals and Wavelets held at Rajagiri School of Engineering and Technology, India from November 9-12, 2013. Written by experts, the contributions hope to inspire and motivate researchers working in this area. They provide more insight into the areas of fractals, self similarity, iterated function systems, wavelets and the applications of both fractals and wavelets. This volume will be useful for the beginners as well as experts in the fields of fractals and wavelets.